Dance PREEMIE, a Dance PaRticipation intervention for Extremely prEterm children with Motor Impairment at prEschool age: an Australian feasibility trial protocol. Issue 1 (26th January 2020) - Cameron, Kate L; McGinley, Jennifer L; Allison, Kim; Fini, Natalie A; Cheong, Jeanie L Y; Spittle, Alicia J
Abstract : Introduction: Children born extremely preterm (EP: <28 weeks gestation) and/or extremely low birth weight (ELBW: <1000 g) are at increased risk of motor impairment compared with children born at term. Children with motor impairment have lower rates of physical activity (PA) participation compared with their typically developing peers. PA participation is an important outcome for children with motor impairment, however, there is limited evidence available to support interventions that improve PA participation in this population. The aim of this study is to assess the feasibility, including the recruitment and retention, acceptability and fidelity, of a preschool dance participation intervention for children born EP/EBLW with motor impairment called Dance PaRticipation intervention for Extremely prEterm children with Motor Impairment at prEschool age. Methods and analysis: This feasibility case series trial will recruit EP/ELBW children with motor impairment (n=10) from the Victorian Infant Collaborative Study 2016/2017 cohort, a prospective longitudinal cohort study. Up to 10 community-based dance teachers will be recruited and provided with physiotherapy-led training and support to facilitate the participation of EP/ELBW children in community dance classes. A mixed-methods approach (quantitative and qualitative) will be used to analyse the primary aim, to determine the feasibility of the intervention from the perspectives of families and dance teachers. Ethics and dissemination: This study is approved by the Human Research Ethics Committees of The Royal Children's Hospital and The Royal Women's Hospital, Melbourne. Study outcomes will be disseminated through conference presentations, peer-reviewed publications and social media. Trial registration number: ACTRN12619001266156